Edukasi Dan Pelatihan Pengelolaan Keuangan Dan Perpajakan Bagi KWT Kripik Nangka - Setiawati, Elvina; Octavia, Yusi Faizhatul; Fauzi, Agus Khazin; Astini, Yuli; Wardah, Sofiati; Hidayanti, Anna Apriana (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
The lack of financial and tax management among KWT actors is a problem and is important to pay attention to. TThis is because KWT actors do not have knowledge and understanding in financial management and taxation such as financial recording, budget allocation, preparation of financial reports, MSME tax rights and obligations as well as billing and tax reporting. Therefore, these various problems are the goal and initial step for the Community Service Team to educate and provide training in financial management and taxation for jackfruit chip farmer entrepreneur groups (KWT) in Lingsar Village, Lingsar District, West Lombok Regency. The methods used in this service activity are lectures, discussions and mentoring. After participating in this service activity, participants are expected to be able to apply and apply the knowledge gained to the business they are running. With the knowledge and application of good and correct financial management, it will be possible to help farmers in farmer entrepreneurial groups to know the condition of their business performance so that appropriate and accurate decisions can be made. Likewise, knowledge of taxation will be able to help and motivate you in fulfilling tax obligations starting from calculating, depositing and reporting your own taxes